2015
DOI: 10.1093/infdis/jiv363
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of the Prevalence of Drug-Resistant Hepatitis B Virus in Antiviral Therapy–Experienced Patients in Europe (CAPRE)

Abstract: These findings support resistance testing in cases of apparent NA therapy failure. This survey highlights the impact of exposure to lamivudine and adefovir on development of drug resistance and cross-resistance. Continued use of these NAs needs to be reconsidered at a pan-European level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
3
21
2
Order By: Relevance
“…In Europe, HBV/D is the most frequently encountered viral genotype (63%), followed by HBV/A (26%). 24 In East Asia, HBV/B and HBV/C are dominant HBV genotypes, while in North China, the prevalence of HBV/C was significantly higher than HBV/B. 16 In a largest-to-date European survey that involved 1,568 NA-experienced chronic hepatitis B patients, drug resistance was observed in half of the cases, 24 similar with that in our current study (45.1%).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In Europe, HBV/D is the most frequently encountered viral genotype (63%), followed by HBV/A (26%). 24 In East Asia, HBV/B and HBV/C are dominant HBV genotypes, while in North China, the prevalence of HBV/C was significantly higher than HBV/B. 16 In a largest-to-date European survey that involved 1,568 NA-experienced chronic hepatitis B patients, drug resistance was observed in half of the cases, 24 similar with that in our current study (45.1%).…”
Section: Discussionsupporting
confidence: 86%
“…This and other European studies showed that there was a mutational pattern bias of rtM204 V for HBV/A and rtM204I for HBV/D. 24,25 By contrast, no such bias was observed between HBV/B-and HBV/C-infected patients in our current study. In NA-untreated patients, drug-resistant mutations were detected in 2/140 (1.4%) of European patients with HBV/D.…”
Section: Discussioncontrasting
confidence: 70%
“…The dominant pattern of resistance (71.4%) among treatment-experienced patients with mutated strains (rtM204V + rtL180M) was higher than that in the European multicenter study (29%) [34] and Ghana (47.6%) [23]. The rtV173LtrtL180MtrtM204V triple change has already been described in patients with HIV and HBV co-infection [35], and resulted in codon changes in the surface open reading frame (ORF; sE164D and sI195M, respectively) [22, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rtV191I mutation may be the new resistance site to LAM. Since rt224I/V has never been reported before [13,[22][23][24][25][26], further observation of these patients might address the question whether these mutations are associated with other nucleoside analogue resistance or affect the outcome of the disease.…”
Section: Discussionmentioning
confidence: 96%